COMMUNITY INITIATIVE AND INVOLVEMENT IN CREATING HEALTHY AND FRIENDLY CITIES: LESSONS FROM YOGYAKARTA (Inisiatip dan Keterlibatan Komunitas dalam Menciptakan Kota yang Sehat dan Akrab) - Bakti Setiawan (Jurnal Manusia dan Lingkungan, 2002)
ABSTRACTAs urbanization continue, more and more people will settle in cities. Cities in developing countries, however, are beset by a host of problems emanating from improper planning and design. Further, cities in developing countries, including Indonesia, also tend to lost their cultural identity and humanity, due to the influence of global market that penetrate the human spirits of the local dwellers. Cities are no longer save and friendly environments to live. This paper addresses this issue. It argues that community initiative and involvement in urban development is crucial for creating healthy and friendly cities. Based on case studies from Yogyakarta, the paper highlights several important factors for communities to be effectively involved in a more “friendly” urban development. From these five case studies, this paper learned that community’s initiatives and involvements could only be effectively conducted if they were better organized and understood the dynamics of urban planning and development. It is therefore very crucial for communities and interest groups to under-stand the “politics” of urban development and to actively involve in the day-to-day decision making process related to urban development.ABSTRAKSejalan dengan peningkatan urbanisasi, akan semakin banyak orang tinggal di kota. Persoalannya adalah bahwa kota kota di Negara berkembang menghadapi berbagai persoalan lingkungan, ekonomi dan sosial, terutama karena pendekatan dan praktek perencanaan dan perancangan kota yang tidak pas. Lebih jauh, kota kota di Negara berkembang sebagaimana di Indonesia cenderung kehilangan identita kulturalnya, terutama karena proses pertumbuhan kota yang dipengaruhi oleh pasar global dan tidak memungkinkan penduduk lokal untuk ikut berpartisipasi dalam pembangunan kotanya. Paper ini berargumen bahwa partisipasi penduduk lokal merupakan prasarat bagi terwujudnya kota yang aman dan akrab. Didasarkan atas studi kasus lima proyek di Yogyakarta yang melibatkan penduduk kota, paper ini merumuskan faktor-faktor penting untuk meningkatkan keterlibatan penduduk lokal. Dari lima studi kasus ini, paper ini berkeyakinan bahwa keterlibatan penduduk lokal akan optimal apabila mereka terorganisir dan memahami dinamika proses pembangunan kota. Adalah penting bagi komunitas untuk memahami proses politik dalam pembangunan kota dan secara aktip terlibat dalam proses keeharian pengambilan keputusan yang menyangkut pembangunan kota.